2012
DOI: 10.5194/bg-9-249-2012
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal CO<sub>2</sub> exchanges measured by Eddy Covariance over a temperate intertidal flat and their relationships to net ecosystem production

Abstract: Abstract. Measurements of carbon dioxide fluxes were performed over a temperate intertidal mudflat in southwestern France using the micrometeorological Eddy Covariance (EC) technique. EC measurements were carried out in two contrasting sites of the Arcachon flat during four periods and in three different seasons (autumn 2007, summer 2008, autumn 2008 and spring 2009). In addition, satellite images of the tidal flat at low tide were used to link the net ecosystem CO 2 exchange (NEE) with the occupation of the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 67 publications
3
43
0
Order By: Relevance
“…Efforts are also focused in using remote sensing reflectances from airbone hyperspectral data to assess MPB PP rates (Méléder et al, 2018). Recently, and in the light of the work of Brito et al (2013) Ibrom, Andreas and Rannik, Üllar and Moncrieff, John and Foken, Thomas and Kowalski, Andy S and Martin, Philippe H and Berbigier, Paul and Bernhofer, Ch and others, 1999;Zemmelink et al, 2009;Polsenaere et al, 2012). Similarly, the aquatic Biogeosciences Discuss., https://doi.org/10.5194/bg-2018-325 Manuscript under review for journal Biogeosciences Discussion started: 10 July 2018 c Author(s) 2018.…”
Section: Top-down Regulation Of Mpb Dynamics 30mentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts are also focused in using remote sensing reflectances from airbone hyperspectral data to assess MPB PP rates (Méléder et al, 2018). Recently, and in the light of the work of Brito et al (2013) Ibrom, Andreas and Rannik, Üllar and Moncrieff, John and Foken, Thomas and Kowalski, Andy S and Martin, Philippe H and Berbigier, Paul and Bernhofer, Ch and others, 1999;Zemmelink et al, 2009;Polsenaere et al, 2012). Similarly, the aquatic Biogeosciences Discuss., https://doi.org/10.5194/bg-2018-325 Manuscript under review for journal Biogeosciences Discussion started: 10 July 2018 c Author(s) 2018.…”
Section: Top-down Regulation Of Mpb Dynamics 30mentioning
confidence: 99%
“…The study of air-water and sediment-water exchanges through simultaneous atmospheric and aquatic EC measurements could 5 allow quantifying the importance of metabolic fluxes during immersion and emersion periods but also the coupled processes between the benthic and pelagic compartments such as MPB resuspension. Microphythobenthic community resuspension can significantly contribute to planktonic gross PP and, in turn, explain lower CO 2 fluxes from the water column to the atmosphere at high tide during the day than at night (Guarini et al, 2008;Polsenaere et al, 2012). To date, the modelling effort put on the physically-driven (tides and waves) resuspension processes of MPB is still limited (see Mariotti and Fagherazzi, 2012).…”
Section: Top-down Regulation Of Mpb Dynamics 30mentioning
confidence: 99%
“…Only very recently have researchers started to also extend eddy covariance measurements to ever more challenging and less widespread ecosystem types, such as mangroves Jha et al, 2014), deserts (Honrath et al, 2002;Liu et al, 2012;Li et al, 2014), intertidal flats (Polsenaere et al, 2012), and screenhouses (Tanny et al, 2006).…”
Section: Deployments In Different Ecosystem Typesmentioning
confidence: 99%
“…Therefore, the method has been widely used to estimate terrestrial atmospheric CO 2 fluxes (Lee et al, 2004). The method has also been used to estimate air-sea CO 2 fluxes in the ocean and coastal seas (McGillis et al, 2001;Vesala et al, 2006;Kondo & Tsukamoto, 2007;Zemmelink et al, 2009;Huotari et al, 2011;Polsenaere et al, 2012) and to estimate sediment-water O 2 fluxes (Berg et al, 2003;Kuwae et al, 2006). However, several studies have reported that results from the eddy covariance method are inconsistent with results from other methods, such as the bulk formula method (Kondo & Tsukamoto, 2007;Zemmelink et al, 2009).…”
Section: Air-sea Co 2 Fluxmentioning
confidence: 99%